Research for a new world: Critical thinking for the water–energy–food–ecosystems nexus (basins) - McCartney, Matthew P.; Ringler, Claudia (CGIAR System Organization, 2022)
A river basin – the breadbasket of millions – battered by floods just a few months earlier, slowly dries up; struck by climate change, over-abstraction of water and degradation of soils and land. As the river flow and reservoir levels fall, hydropower production declines. Farmers start to rely more heavily on groundwater, but access to energy for their irrigation wells is expensive. Many, especially women, are without access and a voice; others pump too much and ratchet up the water stress of the whole basin. Soils turn to dust, crops wilt, livestock and wildlife perish. While communities lack the governance structures for inclusive action, their leaders are hampered by the national borders that cut across the basin. In the heat, the potential for conflict simmers.